1993
DOI: 10.1089/aid.1993.9.365
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Identification of an Immunosuppressive Factor in AIDS Sera

Abstract: The cause of the profound immunodeficiency state induced by the human immunodeficiency virus (HIV) is not yet fully understood. Although direct cytopathic effects of the virus leading to the loss of CD4+ lymphocytes are believed to play a major role, soluble factors that cause lymphocyte dysfunction have also been identified. Here, we demonstrate that sera of AIDS patients contain a viral component capable of profoundly inhibiting normal T lymphocyte and natural killer cell functions. This factor (M(r) 30,000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The patients' NK cells were boosted with IFN-ct to a lesser degree than cells of controls, in accordance with previous studies (8,23), whereas I1-2 boosted the NK cell activity to the same degree in both groups, but without restoration of the defective cytotoxic activity in patients as suggested by others (9,11). It has been suggested that a serum factor contributes to the suppression of the NK and LAK cell functions, but this factor has not been fully identified (16,24,25). Our study showed that there was no correlation between NK cell activity and concentrations of immunoglobulins or HIV antigen in serum.…”
Section: Discussioncontrasting
confidence: 57%
“…The patients' NK cells were boosted with IFN-ct to a lesser degree than cells of controls, in accordance with previous studies (8,23), whereas I1-2 boosted the NK cell activity to the same degree in both groups, but without restoration of the defective cytotoxic activity in patients as suggested by others (9,11). It has been suggested that a serum factor contributes to the suppression of the NK and LAK cell functions, but this factor has not been fully identified (16,24,25). Our study showed that there was no correlation between NK cell activity and concentrations of immunoglobulins or HIV antigen in serum.…”
Section: Discussioncontrasting
confidence: 57%
“…Although it is believed that the cytopathic effect of HIV on the helper/inducer lymphocyte subset plays the major role in the development of the immunodeficiency state in AIDS, viral envetope glycoproteins can also induce immune dysfunctions [19][20][21], Recently an immunosuppressive soluble factor from serum of AIDS patients was identified; it shares epitopes with HIV-I gp41, and markedly inhibits normal T lymphocytes and natural killer function [22]. Gpl20 has been shown to have important immunosuppressive properties 11, 22,23]. It shares an aminoacidic sequence (in positions 7-11) with the vasoactive intestinal peptide (VIP); this neuropeptide inhibits the infection of cultured neuronal cells by HIV-1 by competing for the binding site [24], Receptors for VIP have been found on NK cells [1].…”
Section: Discussionmentioning
confidence: 99%